UNCERTAINTY ANALYSIS OF LABORATORY MEASUREMENT OF AIRBORNE SOUND INSULATION - Bondan Dwisetyo; Maharani Ratna Palupi; Fajar Budi Utomo (Program Studi Fisika Universitas Negeri Jakarta, 2020)
The evaluation and analysis of the uncertainty of laboratory measurement of airborne sound insulation have been carried out by Research Group for Acoustics and Vibration – National Standardization Agency of Indonesia (BSN). The aims of this work are to evaluate and analyze the uncertainty measurement of airborne sound insulation by pressure method, where it is focused only for the determination of sound transmission loss (STL) as a major product of this measurement according to ASTM, and guide to the expressions of Uncertainty in Measurement (GUM) provided by JCGM. The supplied parameter of uncertainty budgets includes measurement of sound pressure level (SPL) in a source room (L1), and measurement of some parameters in a receiver room such as SPL (L2), reverberation time (RT60), background noise (B), test opening area (S), and volume of receiver room (V). From the result of the case study, the source of uncertainty that has a top contribution for obtaining expanded uncertainty is considered as the repeated measurement of the measured parameter such as L1, L2, and RT60 at the frequency range 250 Hz – 315 Hz. Meanwhile, the standard uncertainty that provided by the calibration certificate also contributes to the final result, where it is supplied by an acoustic calibrator and sound analyzer, respectively. Furthermore, the sources obtained from the readability parameter has a slight effect on this whole result. Therefore, the maximum and minimum value of expanded uncertainty is determined that their values are 0.70 dB and 0.43 dB for the frequency of 315 Hz and 1600 Hz, respectively.